Activation-induced cytidine deaminase in tertiary lymphoid structures: dual roles and implications in cancer prognosis - Lv, Zhuangwei; Jiao, Junna; Xue, Wuyang; Shi, Xiaoyu; Wang, Ruihan; Wu, Jinhua (Frontiers in Oncology, 2025)
Activation-induced cytidine deaminase (AID) serves as a critical molecular orchestrator in the germinal center (GC) reaction within secondary lymphoid organs (SLOs), driving the production of high-affinity antibodies through somatic hypermutation. While its pathological implications are well-documented - including ectopic expression in non-B cell populations and transcriptional dysregulation linked to hematological malignancies and solid tumorigenesis - the cellular provenance of AID in solid tumors remains an unresolved paradox. This review advances two principal hypotheses: (1) AID may derive from tertiary lymphoid structures (TLSs), ectopic immune niches mirroring SLO organization, and (2) exhibits context-dependent transcriptional duality, capable of both potentiating and suppressing gene expression based on microenvironmental cues. Through systematic analysis of AID/GC involvement across cancer subtypes, we delineate mechanistic connections between lymphoid neogenesis and tumor progression. Our examination extends to TLS architecture, revealing three critical dimensions: (i) structural organization and cellular heterogeneity, (ii) developmental trajectories, and (iii) bidirectional interactions with tumor microenvironments. Crucially, we establish functional parallels between tumor-infiltrating B cells (TIL-Bs) in SLOs versus TLSs, while elucidating the differential roles of AID in canonical GC versus TLS-associated GC formation. This synthesis ultimately proposes that AID’s functional dichotomy - acting as both oncogenic collaborator and tumor suppressor - underlies the paradoxical prognostic associations observed with TLS presence across malignancies. The review thereby provides a conceptual framework reconciling AID’s dual functionality with the context-dependent immunobiology of tumor-associated lymphoid structures.